Five year follow-up after autologous peripheral blood hematopoietic stem cell transplantation for refractory, chronic, corticosteroid-dependent systemic lupus erythematosus: effect of conditioning regimen on outcome. (June 2018) - Burt, Richard; Han, Xiaoqiang; Gozdziak, Paula; Yaung, Kim; Morgan, Amy; Clendenan, Allison; Henry, Jacquelyn; Calvario, Michelle; Datta, Syamal; Helenowski, Irene; Schroeder, James
Abstract Some patients with systemic lupus erythematosus (SLE) are refractory to traditional therapies, dependent on chronic corticosteroids, have organ damage, and are at high risk of mortality. In this group of patients, we report outcome at a median of five years after autologous hematopoietic stem cell transplant (HSCT) using two different non-myeloablative regimens. Four patients received a conditioning regimen of cyclophosphamide (200 mg/kg) and alemtuzumab (60 mg), while 26 patients underwent conditioning with cyclophosphamide (200 mg/kg), rATG (Thymoglobulin) (5.5 mg/kg), and rituximab 1000 mg. Unselected peripheral blood stem cells were infused on day 0. There were no treatment related deaths. Of the four patients treated with cyclophosphamide and alemtuzumab, none entered remission. For the 26 patients treated with cyclophosphamide, rATG, and rituximab, disease remission defined as no immune suppressive drugs except hydroxychloroquine and/or 10 mg or less of prednisone a day was 92% at 6 months, 92% at one year, 81% at 2 years, 71% at 3 years, and 62% at 4 and 5 years post-HSCT. Autologous HSCT outcome is dependent on the conditioning regimen but prior organ damage may cause lingering symptoms.